The Effect of Company Size, Leverage, and Profitability on Company Value in the Plantation Sector Listed on the Indonesia Stock Exchange for the Period 2021-2023 - Susilawati, Susilawati; Rahmazaniati, Linda; Hastuti, Cut Sri Firman; Amri, Abrar; Sartika, Dewi (The Future of Education Journal, 2024)
Companies operating in the plantation sector, as one of the strategic sectors in Indonesia's economy, are required to maximize company value. Company value can be influenced by company size, leverage, and profitability. This study aims to examine the effect of each independent variable on the dependent variable. The research methodology used in this study is quantitative. The population in this study consists of 24 companies in the agriculture sector. The sample selection used purposive sampling, resulting in 10 companies. The data analysis method employed is multiple linear regression, including classical assumption tests, regression tests, and hypothesis testing. The results show that company size has a partial effect on company value with a t-value of (4.652 > 2.055). The results also indicate that leverage has a partial effect on company value with a t-value of (4.642 > 2.055). Similarly, profitability has a partial effect on company value with a t-value of (2.527 > 2.055). Simultaneously, company size, leverage, and profitability have a positive and significant effect on company value with a p-value of 0.000 < 0.05. Additionally, based on the coefficient of determination test, the variables of company size, leverage, and profitability are able to explain 75.6% of the variation in company value, while 24.4% is influenced by other variables not included in this study.